The Potential for Dams to Impact Lowland Meandering River Floodplain Geomorphology - Philip M. Marren; James R. Grove; J. Angus Webb; Michael J. Stewardson (The Scientific World Journal)
The majority of the world's floodplains are dammed. Although some implications of dams for riverine ecology and for river channel morphology are well understood, there is less research on the impacts of dams on floodplain geomorphology. We review studies from dammed and undammed rivers and include influences on vertical and lateral accretion, meander migration and cutoff formation, avulsion, and interactions with floodplain vegetation. The results are synthesized into a conceptual model of the effects of dams on the major geomorphic influences on floodplain development. This model is used to assess the likely consequences of eight dam and flow regulation scenarios for floodplain geomorphology. Sediment starvation downstream of dams has perhaps the greatest potential to impact on floodplain development. Such effects will persist further downstream where tributary sediment inputs are relatively low and there is minimal buffering by alluvial sediment stores. We can identify several ways in which floodplains might potentially be affected by dams, with varying degrees of confidence, including a distinction between passive impacts (floodplain disconnection) and active impacts (changes in geomorphological processes and functioning). These active processes are likely to have more serious implications for floodplain function and emphasize both the need for future research and the need for an “environmental sediment regime” to operate alongside environmental flows.